Simple halogen-free synthesis of aryl cinnamates using Mo-Keggin heteropoly acids as catalyst - Palermo, Valeria (2012)
A convenient chlorine-free procedure for the direct esterification of cinnamic acids with phenols is described. The method does not require stoichiometric activation of the carboxyl group with thionyl chloride or condensing reagents. The methodology is very simple, environmentally friendly, and high-yielding for both electron-releasing and -withdrawing substituted phenols. The Keggin heteropoly acids H3PMo12O40 and H4SiMo12O40 were employed as catalyst in simple bulk form. The effects of temperature, reaction time, and amount of the catalyst used on the ester yield were checked. Suitable conditions for the reaction include a 1:1 molar ratio of reactants and a 1 mmol % of catalyst to reactant ratio. Seventeen aryl cinnamates were obtained, yields ranged from 80 to 91 % for most of the esters. The catalyst was shown to be reusable for at least four times without any appreciable loss of its activity.